Financiamento da educação pública primária no Estado de Minas Gerais (1890-1920) - Alisson José da Silva Esteves Pereira (2023)
The thesis investigates the financing of primary public education in Minas Gerais between 1890 and 1920, a period of political activities of the so-called “first oligarchic republican political generation” and propagation of the discourses that praised the expansion of education as a factor of progress. Within the scope of these events, the links constituted between coronelistic and clientelistic policies, discussions about the responsibility for financing primary public schools, and the implementation of public policies directed towards primary education are problematized. In this context, legislation was published at the national level, such as the Benjamin Constant Reform of 1890, Federal Law No. 1617 of 1906 and Law No. 2738 of 1913, where the issue of financing was addressed. In Minas Gerais, the first Constitution of Minas Gerais was edited, in 1891, in which the debates covered the attribution of funding for public education in the State, and 16 Minas Gerais legislations were published with indication of financing guidelines, namely: the Decree No. 260 of 1890; the Afonso Penna Reform (Law No. 41 of 1892 regulated by Decree No. 655 of 1893), Law No. 90 of 1894, Law No. 203 of 1896, Law No. 221 of 1897, Decree No. Silviano Brandão (Law No. 281 regulated by Decree No. 1.348 of 1900), the João Pinheiro Reform (Law No. 439 of 1906 regulated by Decree No. 1.960), Decree No. 1.969 of 1907, Decree No. 2.416 of 1909, the Bueno Reform Brandão (Law No. 533 of 1910 regulated by Decree No. 3.191 of 1911) and the Arthur Bernardes Reform (Law No. 800 of 1920). In the set of discussions on responsibility for financing primary schools, educational reforms took place, both in the Federal District and in Minas Gerais, which aimed to link the desired school changes and the expected costs. For the development of the theme, the thesis was organized into three chapters. The first deals with the proposals for funding primary education in Brazil, in general, through the study of the current legislation, through the analysis of statistical data and through the examination of the discussions that took place in the period by politicians, journalists and educators. This debate was investigated in three national congresses that took place in the 1910s. The second chapter deals more specifically with the funding proposals carried out in Minas Gerais as part of the process of state organization of primary education, aiming to demonstrate the procedure of the Minas Gerais oligarchy in the establishment of priorities of costs and expenses with primary education. The third chapter analyzes the process of transferring financial resources to primary schools located in different regions of the State, as well as the Caixas Escolares, created to help poor students. For this thesis, documentary research was carried out in different sources, such as: legislation, reports and government letter of the funds of the Secretariat of the Interior and Finance, contained in the collection of the Public Archive of Minas Gerais; Minutes of the Assembly and Chamber, the Legislative Assembly collection and newspapers of the time (digital collections), and theoretical studies in the fields of sociology and economics, as well as the history and history of education. It is noteworthy that the study on the funding of primary education made it possible to analyze the public policies organized by politicians from Minas Gerais to carry out the financing of primary education and, at the same time, showed that this funding did not happen equitably by the State, since, under the influence of coronelista policies, the politically active regions under the government of Minas, such as Sul de Minas, Zona da Mata and the Central region of the State, benefited from greater investment in education and, therefore, more schools were financed by the State Treasury compared to other regions.